VALIDATION OF THE NEPHELOMETRIC METHOD FOR DETERMINING BLOOD PLASMA COAGULATION AND APPLICATION OF A MATHEMATICAL MODEL FOR ITS ANALYSIS - FEDORENKO, VOLODYMYR; BEHDAI, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Increasing the bioavailability of oral drugs is a key task in pharmaceutical development, especially for active pharmaceutical ingredients (APIs) with low solubility. One effective method is to create solid dispersion systems (SDS) that improve the solubility of APIs. An example of such an ingredient is rivaroxaban, a direct oral anticoagulant. However, in order to objectively assess how improved solubility affects pharmacological activity, reliable and validated analytical methods are needed that are capable of quantitatively analysing the key pharmacodynamic effect – the change in blood plasma coagulation kinetics. Therefore, the aim of the study was to validate an in vitro analytical method for studying the kinetics of blood plasma coagulation using a laser nephelometer. The key task was to prove that the method is reliable, accurate and reproducible, which will allow it to be used for a reasonable assessment of the effect of new rivaroxaban dosage forms, in particular TDS, on its anticoagulant activity.The method was validated on a NEPHELOstar laser nephelometer. The validation procedure included verification of key parameters: specificity, robustness, precision and linearity. To process the obtained S-shaped kinetic curves and calculate analytical parameters, in particular the maximum coagulation rate (vmax), a four-parameter mathematical Weibull model was used.The study confirmed the compliance of the method with all validation criteria. Its specificity, high robustness to minor changes in analysis conditions (temperature and measurement time) and precision were proven. A clear relationship was established between the concentration of rivaroxaban (in the range of 5–15 μM) and the maximum rate of coagulation with a high coefficient of determination, confirming its suitability for studying the coagulation process. The validated nephelometric in vitro method is an accurate, reproducible and reliable tool for studying the kinetics of blood plasma coagulation and assessing the effect of anticoagulants, in particular rivaroxaban. The method can be recommended for use in pharmaceutical development for comparative analysis and quality control of innovative dosage forms aimed at increasing the solubility and bioavailability of APIs.
Keywords: solid dispersion system; rivaroxaban; coagulation; nephelometer; active pharmaceutical ingredient; Weibull model